2010
DOI: 10.1556/achrom.22.2010.1.11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis ofSaussureaspecies from tibet using HPLC-DAD-ESI-MSn

Abstract: An HPLC-DAD-ESI-MS n method has been developed for simultaneous quantification of eight major compounds in eight Saussurea species which have long been used as the traditional Tibetan medicines. The method was validated for sensitivity, precision, and accuracy. LODs were from 0.11 to 5.01 μg mL −1 , overall intra-day and inter-day variation was less than 2.70%, and overall recovery was over 98.0%. The correlation coefficients (r 2) of the calibration plots were >0.991. This newly established method was success… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Additionally, it was found that extraction temperatures above 60 °C should be avoided and degassed extraction solvents should be used with pressurized liquid extraction (PLE) due to the chemical reactivity of the phenolics (17,18). The analysis of polyphenols from botanical sources, particularly solanaceous plants like tobacco, using mass spectrometry has been the subject of a significant amount of research and ESI-MS/MS has been used to generate fragmentation data on major and minor polyphenols found in plant extracts (19)(20)(21)(22)(23)(24)(25)(26). Similarities in the fragmentation of the three isomers of chlorogenic acid are well documented (19)(20)(21)(22) and emphasize the need for the optimized chromatographic separation presented here to both distinguish and quantify these compounds in tobacco extracts.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was found that extraction temperatures above 60 °C should be avoided and degassed extraction solvents should be used with pressurized liquid extraction (PLE) due to the chemical reactivity of the phenolics (17,18). The analysis of polyphenols from botanical sources, particularly solanaceous plants like tobacco, using mass spectrometry has been the subject of a significant amount of research and ESI-MS/MS has been used to generate fragmentation data on major and minor polyphenols found in plant extracts (19)(20)(21)(22)(23)(24)(25)(26). Similarities in the fragmentation of the three isomers of chlorogenic acid are well documented (19)(20)(21)(22) and emphasize the need for the optimized chromatographic separation presented here to both distinguish and quantify these compounds in tobacco extracts.…”
Section: Introductionmentioning
confidence: 99%
“…[36] Peak 7 was identified as 4-hydroxyacetophenone with a main deprotonated ion at m/z 135.0460, in accordance with the reported spectral data. [22] Peak 20 showed base peaks at m/z 455.1988, 819.3888 and 409.1950, in accordance with fragmentations of involucratolactone-β-D-glucoside. [38] Peak 16 showed a base peak at m/z 461.1116, which was assigned as a deprotonated product of homoplantaginin.…”
Section: Qualitative Analysismentioning
confidence: 66%
“…[38] Peak 16 showed a base peak at m/z 461.1116, which was assigned as a deprotonated product of homoplantaginin. [22] Peak 20 showed base peaks at m/z 455.1988, 819.3888 and 409.1950, in accordance with fragmentations of involucratolactone-β-D-glucoside. [39] Peak 21 was identified as another sesquiternene, displaying a quasi-molecular ion m/z 411.2095 and a formiate ion m/z 457.2153.…”
Section: Qualitative Analysismentioning
confidence: 66%
See 2 more Smart Citations